Conservation Easements: Options for Preserving Current Land Uses - Chris Demers; Douglas R. Carter (EDIS)
This publication describes conservation easements, what is involved in establishing one, some of the tax implications of such agreements, the government and non-government organizations that commonly participate in conservation easements, and important considerations for landowners before entering into such an agreement. This document is SS-FOR-21, one of a Forest Stewardship Program series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: January 2004.